Association of growth hormone deficiency with an increased number of preadipocytes in subcutaneous fat - Zhao, Lidan; Jia, Dan; Tan, Zhendong; Jiang, Honglin (Frontiers in Endocrinology, 2023)
The inhibitory effect of growth hormone (GH) on adipose tissue growth is well known, but the underlying mechanism is not fully understood. In this study, we determined the possibility that GH inhibits adipose tissue growth by inhibiting adipogenesis, the process of formation of adipocytes from stem cells, in the lit/lit mice. The lit/lit mice are GH deficient because of a spontaneous mutation to the GH releasing hormone receptor (ghrhr) gene, and they have more subcutaneous fat despite being smaller than the lit/+ mice at the same age. We found that cells of the stromal vascular fraction (SVF) of subcutaneous fat from the lit/lit mice had greater adipogenic potential than those from the lit/+ mice, as evidenced by forming greater numbers of lipid droplets-containing adipocytes and having greater expression of adipocyte marker genes during induced adipocyte differentiation in culture. However, addition of GH to the culture did not reverse the superior adipogenic potential of subcutaneous SVF from the lit/lit mice. Through florescence-activated cell sorting and quantification of mRNAs of preadipocyte markers, including CD34, CD29, Sca-1, CD24, Pref-1, and PPARγ, we found that subcutaneous SVF from the lit/lit mice contained more preadipocytes than that from the lit/+ mice. These results support the notion that GH inhibits adipose tissue growth in mice at least in part by inhibiting adipogenesis. Furthermore, these results suggest that GH inhibits adipogenesis in mice not by inhibiting the terminal differentiation of preadipocytes into adipocytes, rather by inhibiting the formation of preadipocytes from stem cells or the recruitment of stem cells to the fat depot.